2021
DOI: 10.48550/arxiv.2106.11923
|View full text |Cite
Preprint
|
Sign up to set email alerts
|

Diagnosing the Quark-Gluon Plasma

Abstract: Brief review of the hadronic probes that are used to diagnose the quark-gluon plasma produced in relativistic heavy ion collisions and interrogate its properties. Emphasis is placed on probes that have significantly impacted our understanding of the nature of the quark-gluon plasma and confirmed its formation.

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
2

Citation Types

0
2
0

Year Published

2022
2022
2022
2022

Publication Types

Select...
2

Relationship

0
2

Authors

Journals

citations
Cited by 2 publications
(2 citation statements)
references
References 37 publications
0
2
0
Order By: Relevance
“…Nowadays, such an extreme state of matter may occur naturally in the core of compact stellar objects like neutron stars or during neutron star merger events. In a laboratory environment, extreme temperatures and densities can be created in relativistic collisions of heavy particles, see for example [1,2,3,4,5] for reviews. Such heavy-ion collisions are furthermore the only means by which bulk properties of a non-Abelian gauge theory, such as Quantum Chromodynamics (QCD), can be assessed experimentally.…”
Section: Introductionmentioning
confidence: 99%
“…Nowadays, such an extreme state of matter may occur naturally in the core of compact stellar objects like neutron stars or during neutron star merger events. In a laboratory environment, extreme temperatures and densities can be created in relativistic collisions of heavy particles, see for example [1,2,3,4,5] for reviews. Such heavy-ion collisions are furthermore the only means by which bulk properties of a non-Abelian gauge theory, such as Quantum Chromodynamics (QCD), can be assessed experimentally.…”
Section: Introductionmentioning
confidence: 99%
“…Recent reviews can be found in Refs. [2][3][4] To study properties of the QGP by using quarkonium, theoretical inputs are necessary in addition to the experimental measurements. The real-time dynamics of quarkonium inside the QGP is complicated since the description has to account for plasma screening, dissociation and regeneration of quarkonium states.…”
Section: Introductionmentioning
confidence: 99%